2016
DOI: 10.1016/j.arth.2016.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cirrhosis on Resource Use and Inpatient Complications in Patients Undergoing Total Knee and Hip Arthroplasty

Abstract: Background Cirrhosis is a major cause of morbidity and mortality and is an important risk factor for complications in surgical patients. The purpose of this study was to investigate the association of cirrhosis with postoperative complications, length of stay (LOS), and costs among patients who underwent total knee (TKA) or hip (THA) arthroplasty. Methods Using the Nationwide Inpatient Sample between 2000 and 2011, we identified patients who had a primary TKA or primary THA. TKA patients were divided into tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 32 publications
0
14
1
Order By: Relevance
“…Newman et al demonstrated that patients with cirrhosis undergoing TKA had a mean of $1,857 higher costs and 0.30-day longer length of stay compared with noncirrhosis patients. 23 Parvizi et al also reported higher risk of mechanical complications odds ratios (ORs 4.38), increased risk of manipulation under anesthesia (OR 2.03), revision TKA for any reason (OR 4.42), and longer hospital stay (p < 0.01) in patients with hepatitis C cirrhosis who underwent a TKA in their institution. 25 Similarly, Deleuran et al used a Danish health care registry to analyze 393 cirrhosis patients compared with over 100,000 matched controls, and demonstrated that patient with cirrhosis tended to be younger, more often received general anesthesia, had more comorbidities, and were more commonly hospitalized preoperatively.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Newman et al demonstrated that patients with cirrhosis undergoing TKA had a mean of $1,857 higher costs and 0.30-day longer length of stay compared with noncirrhosis patients. 23 Parvizi et al also reported higher risk of mechanical complications odds ratios (ORs 4.38), increased risk of manipulation under anesthesia (OR 2.03), revision TKA for any reason (OR 4.42), and longer hospital stay (p < 0.01) in patients with hepatitis C cirrhosis who underwent a TKA in their institution. 25 Similarly, Deleuran et al used a Danish health care registry to analyze 393 cirrhosis patients compared with over 100,000 matched controls, and demonstrated that patient with cirrhosis tended to be younger, more often received general anesthesia, had more comorbidities, and were more commonly hospitalized preoperatively.…”
Section: Discussionmentioning
confidence: 94%
“…The findings of increased episode-of-care costs for patients who have comorbidities such as cirrhosis, hepatitis C, COPD, CKD, and morbid obesity directly relate to prior studies that have demonstrated greater complication rates in these patient populations. [20][21][22][23][24][25][26] The ability to limit postoperative complications has been of great interest in the arthroplasty literature as these events not only impact patients' quality of life but also increase health care expenditure drastically. 16,17,20,21 Although cost containment is critical for hospitals' long-term financial sustainability, it must not come at the expense of patient care.…”
Section: Discussionmentioning
confidence: 99%
“…Nonmodifiable risk factors include age and some chronic disease processes such as CHF, COPD, CKD, and cirrhosis. 56,58,65,66,94,[97][98][99][100][101][102][103][104][105]…”
Section: Nonmodifiable Risk Factorsmentioning
confidence: 99%
“…Patients were sequentially excluded if they were less than 18 years old or met any of the following conditions (identified using ICD-9-CM diagnosis codes): admission type, for example; emergency, urgent, trauma center, or others; admission source of "emergency room"; pathological fractures; fractures of femur; other fractures; multiple ill-defined fractures of the lower limb; multiple fractures involving both lower limbs; acute infection of lower extremity or buttocks; diagnosis suggestive of previous arthroplasty; metastatic cancer; or fractures of the tibia and fibula. 25,26 The final study population included 5,043,210 patients who underwent TKA, of whom 5,018,496 had no hematologic malignancy and 24,714 had any hematologic malignancy. When stratified by the subtype of hematologic malignancy, the number of TKA patients in each subcategory were as follows: Hodgkin's disease (N ¼ 791), Non-Hodgkin's lymphoma (N ¼ 7,096), plasma cell dyscrasias (N ¼ 1,621), leukemia (N ¼ 8,005), myeloproliferative disease (N ¼ 5,746), and/or myelodysplastic syndromes (N ¼ 1,608).…”
Section: Study Populationmentioning
confidence: 99%